If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-3(x+2)=9
We simplify the equation to the form, which is simple to understand
5-3(x+2)=9
Reorder the terms in parentheses
5+(-3x-6)=9
Remove unnecessary parentheses
+5-3x-6=+9
We move all terms containing x to the left and all other terms to the right.
-3x=+9-5+6
We simplify left and right side of the equation.
-3x=+10
We divide both sides of the equation by -3 to get x.
x=-3.3333333333333
| 6(1-2n)=-2(n-2) | | x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) | | sqrt(6+x)*sqrt(4-x)=3 | | 10+-2z=-30 | | 11x-5=60 | | 5m-4=3m+12 | | w^3+5w^2+-23w-3= | | -2=-9-2(-2x+1) | | -7f+-31=53 | | X^3-2x+21=0 | | 20+-10c=100 | | 2b+a=5 | | 2,711/9= | | 0.9=0.8+x-0.8x | | (-4x)(-2x^2)= | | x-21=2x+3 | | (w-3)(w^2+8w+1)= | | 7(x+6)=8(x-4) | | t^2+48t=0 | | (4x)=26 | | 7n^7+9n+5= | | 10.4+4= | | -x^2-12-18=0 | | 10/x=25/20 | | 9(s+10)+7=3s-11 | | f(x)=-2-2x |